2020
DOI: 10.1002/jbmr.4380
|View full text |Cite
|
Sign up to set email alerts
|

Safety of therapy with and withdrawal from denosumab in fibrous dysplasia and McCune-Albright syndrome: an observational study

Abstract: Denosumab (Dmab) treatment can benefit patients with fibrous dysplasia/McCune-Albright syndrome (FD/MAS) by suppressing the receptor activator of nuclear factor κB ligand (RANKL)-mediated increased bone resorption. However, limited data of two pediatric cases indicate that a rebound phenomenon may occur after withdrawal. Therefore we studied the safety of Dmab discontinuation in FD/MAS. Thirty-seven patients using Dmab, mostly after unsuccessful bisphosphonate (BP) treatment, were included. Health records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…The onset of rebound ranged from 3 to 8 months post-discontinuation, and was associated with severe hypercalcemia in 1 subject, highlighting an important and potentially life-threatening complication. Previous reports of postdiscontinuation hypercalcemia in FD have been limited to 2 children 6,13 , and a retrospective review of clinically-treated adults did not identify symptomatic hypercalcemia 22 . In our study, the subject with severe hypercalcemia had extremely elevated baseline bone turnover, with the highest Skeletal Burden Score and P1NP level in the cohort.…”
Section: Discussionmentioning
confidence: 95%
“…The onset of rebound ranged from 3 to 8 months post-discontinuation, and was associated with severe hypercalcemia in 1 subject, highlighting an important and potentially life-threatening complication. Previous reports of postdiscontinuation hypercalcemia in FD have been limited to 2 children 6,13 , and a retrospective review of clinically-treated adults did not identify symptomatic hypercalcemia 22 . In our study, the subject with severe hypercalcemia had extremely elevated baseline bone turnover, with the highest Skeletal Burden Score and P1NP level in the cohort.…”
Section: Discussionmentioning
confidence: 95%
“…[ 11 , 12 ] Meier et al investigated adverse events of denosumab (60 mg every 3–6 months) in 37 patients with FD and found that 1 patient (2.7%) had hypercalcemia 5 months after its discontinuation. [ 17 ] In the present case, close clinical monitoring with laboratory data was performed after discontinuation of denosumab treatment. No increase in serum calcium level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…No increase in serum calcium level was observed. In a study by Meier et al, 1 patient (2.7%) with FD developed osteonecrosis of the jaw with a median cumulative dose of 660 mg. [17] Palmerini et al reported a 6% incidence of osteonecrosis of jaw in 97 patients with GCTB who were treated with denosumab for a median of 20 months. [19] TRACP-5b has been used as a marker of bone resorption in patients with osteoporosis or GCTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data found that denosumab was not associated with increased risk of serious adverse events. However, recently, several studies reported that the rapid bone loss and the rebound fractures may occur when treatment is stopped ( 39 , 40 ), which needs to be considered when choosing this agent.…”
Section: Discussionmentioning
confidence: 99%